(Table 1) Lithology and total organic carbon at DSDP Hole 61-462 - I D Thomson; Simon C Brassell; P A Comet; Geoffrey Eglinton; P J Isaacson; James McEvoy; James R Maxwell (PANGAEA, 1981)
The solvent-extractable lipids of Sections 462-49-4 (lower Maestrichtian), 462-54-2 (Campanian), and 462-59-1 (Cenomanian), from the Nauru Basin, were investigated for aliphatic and aromatic hydrocarbons, ketones, alcohols, and acids, after separation into acid and neutral fractions. Detailed analyses of the total neutral fraction revealed only n-alkanes, steranes, and triterpanes present in sufficient concentration (>0.5 ng/100 g dry sediment for individual compounds) for component recognition. N-alkanes (C19-C35) constitute the major component of each section, with the most abundant present as 10 (n-C24), 135 (n-C29), 17 (n-C26) ng/100 g dry sediment in Sections 462-49-4, 462-54-2, and 462-59-1, respectively. The results suggest a high degree of thermal maturity of the lipids, which is interpreted in terms of the high geothermal gradient (about 50°C/km) and the regional volcanicity. The lipid data also suggest that the major source of organic matter was terrestrial and that deposition took place in a low-productivity oxic environment.
Supplement to: Thomson, ID et al. (1981): Preliminary lipid analyses of Cores 49, 54, and 59 from Hole 462. In: Larson, RL; Schlanger, SO; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 61, 613-618, https://doi.org/10.2973/dsdp.proc.61.118.1981